Treatment Response After Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC) for Peritoneal Metastases of Colorectal Originf - Martin Hübner, MD; S. P. Somashekhar, MD; Hugo Teixeira Farinha, MD; Julio Abba, MD; Ramya G. Rao, PhD; Mohammad Alyami, MD; Wouter Willaert, MD, PhD; on behalf of the PIPAC study group; Brigand Cecile, MD; Delhorme Jean-Baptiste, MD, PhD; Romain Benoit, MD, PhD; Charleux-Muller Diane, MD; et al. (Annals of Surgery Open, 2022)
Objective:. The objective of this study is to analyze oncological outcomes of patients with peritoneal metastases (PM) of colorectal origin treated with Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC). Background:. PIPAC has been demonstrated to be a feasible and safe novel treatment for patients with PM of various origins. Only small series reports on survival after PIPAC by disease entity. Methods:. International retrospective cohort study of consecutive patients with PM of colorectal origin. Outcome measures were overall survival (OS), radiological response according to Response Evaluation Criteria in Solid Tumors (RECIST), histological response (peritoneal regression grading score [PRGS]: complete response: 1–4: no response), change of peritoneal cancer index (PCI), and symptom control. Results:. Seventeen eligible centers compiled 256 non-selected patients (mean age 61 [50.6–69.2], 43% female) and 606 procedures. Sixty-three percent were treated after 2 lines of chemotherapy, median PCI at PIPAC1 was 18 (interquartile range [IQR] = 10–27). Median OS was 19.00 months (IQR = 12.9–29.8) from diagnosis and 9.4 months (IQR = 4.5–16.8) from PIPAC1. One hundred and four of 256 patients (40.6%) had ≥3 procedures (per protocol [pp]) with the following outcomes at PIPAC3: RECIST: 59.3% partial response/stable, 40.7% progression; mean PRGS: 2.1 ± 0.9. Median PCI was 21 (IQR = 15–29) at baseline and 20 (IQR = 12–27) at PIPAC3 (P = 0.02). Fifty-six (54%) and 48 (46%) patients were symptomatic at baseline and PIPAC3, respectively (P = 0.267). Median OS for the pp cohort was 11.9 months (IQR = 10.7–15.0) from PIPAC1. Independent predictors for survival were radiological response (HR = 3.0; 95% CI = 1.6–5.7) and no symptoms (HR = 4.5, 95% CI = 2.2–9.1) at PIPAC3. Conclusions:. Objective treatment response and encouraging survival were demonstrated after PIPAC for colorectal PM. Prospective registry data and comparative studies are now needed in to confirm these data.